Electrolyte disorders related emergencies in children - Zieg, Jakub; Ghose, Shaarav; Raina, Rupesh (BMC nephrology, 2024)
This article provides a comprehensive overview of electrolyte and water homeostasis in pediatric patients, focusing on some of the common serum electrolyte abnormalities encountered in clinical practice. Understanding pathophysiology, taking a detailed history, performing comprehensive physical examinations, and ordering basic laboratory investigations are essential for the timely proper management of these conditions. We will discuss the pathophysiology, clinical manifestations, diagnostic approaches, and treatment strategies for each electrolyte disorder. This article aims to enhance the clinical approach to pediatric patients with electrolyte imbalance-related emergencies, ultimately improving patient outcomes.Trial registration This manuscript does not include a clinical trial; instead, it provides an updated review of literature.
Keywords: Hypernatremia; hyperkalemie; Emergencies; hyperkalcemie; Hypercalcemia; Electrolyte imbalances; Acid-Base Imbalance; poruchy acidobazické rovnováhy; Hyperkalemia; náhlé příhody; acidóza; Hypokalemia; hypernatremie; dítě; hyponatremie; Child; hypokalemie; Pediatrics; Hypocalcemia; vodní a elektrolytová rovnováha; Acidosis; Humans; Water-Electrolyte Imbalance; Hyponatremia; vodní a elektrolytová nerovnováha; hypokalcemie; elektrolyty; Electrolytes; Water-Electrolyte Balance; lidé